Clinical Applications of Carbon Nanomaterials in Diagnostics and Therapy. Issue 47 (21st August 2018) - Loh, Kian Ping; Ho, Dean; Chiu, Gigi Ngar Chee; Leong, David Tai; Pastorin, Giorgia; Chow, Edward Kai‐Hua
Abstract: Nanomaterials have the potential to improve how patients are clinically treated and diagnosed. While there are a number of nanomaterials that can be used toward improved drug delivery and imaging, how these nanomaterials confer an advantage over other nanomaterials, as well as current clinical approaches is often application or disease specific. How the unique properties of carbon nanomaterials, such as nanodiamonds, carbon nanotubes, carbon nanofibers, graphene, and graphene oxides, make them promising nanomaterials for a wide range of clinical applications are discussed herein, including treating chemoresistant cancer, enhancing magnetic resonance imaging, and improving tissue regeneration and stem cell banking, among others. Additionally, the strategies for further improving drug delivery and imaging by carbon nanomaterials are reviewed, such as inducing endothelial leakiness as well as applying artificial intelligence toward designing optimal nanoparticle‐based drug combination delivery. While the clinical application of carbon nanomaterials is still an emerging field of research, there is substantial preclinical evidence of the translational potential of carbon nanomaterials. Early clinically trial studies are highlighted, further supporting the use of carbon nanomaterials in clinical applications for both drug delivery and imaging. Abstract : Biomedical application of carbon nanomaterials as well as the potential clinical implementation of carbon nanomaterials includes enhanced drug delivery, improved sensitivity of clinical diagnostic tools and imaging drugs, as well as more effective regenerative medical platforms.